2023
DOI: 10.3389/fpls.2023.1091567
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of NBS-LRR genes revealed contribution of disease resistance from Saccharum spontaneum to modern sugarcane cultivar

Abstract: IntroductionDuring plant evolution, nucleotide-binding sites (NBS) and leucine-rich repeat (LRR) genes have made significant contributions to plant disease resistance. With many high-quality plant genomes sequenced, identification and comprehensive analyses of NBS-LRR genes at whole genome level are of great importance to understand and utilize them.MethodsIn this study, we identified the NBS-LRR genes of 23 representative species at whole genome level, and researches on NBS-LRR genes of four monocotyledonous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…Based on the bioinformatic analysis of the C. ensifolium genome, this study identified a total of 31 CeNBS-LRR genes, including zero members of the TNL family and one member of the RNL family, while the remaining genes belonged to the CNL family. Similar situations have been found in various monocots such as rice, wheat, grapes, sugarcane, and sorghum, indicating a gradual loss of the TNL family members in the evolutionary history of monocot plants [44][45][46]. Although it has been suggested that the number of NBS-LRR genes is positively correlated with genome size, the number of CeNBS-LRR genes is extremely low compared to common agricultural and horticultural crops, and it is speculated that this may be related to the growing environment and the small number of ancestors [13].…”
Section: Discussionsupporting
confidence: 65%
“…Based on the bioinformatic analysis of the C. ensifolium genome, this study identified a total of 31 CeNBS-LRR genes, including zero members of the TNL family and one member of the RNL family, while the remaining genes belonged to the CNL family. Similar situations have been found in various monocots such as rice, wheat, grapes, sugarcane, and sorghum, indicating a gradual loss of the TNL family members in the evolutionary history of monocot plants [44][45][46]. Although it has been suggested that the number of NBS-LRR genes is positively correlated with genome size, the number of CeNBS-LRR genes is extremely low compared to common agricultural and horticultural crops, and it is speculated that this may be related to the growing environment and the small number of ancestors [13].…”
Section: Discussionsupporting
confidence: 65%